Infection and interferon production in systemic juvenile chronic arthritis: a prospective study. Issue 1 (February 1984) - de Vere-Tyndall, A; Bacon, T; Parry, R; Tyrrell, D A; Denman, A M; Ansell, B M
Abstract : Twenty-four episodes of disease exacerbation in 19 children suffering from systemic juvenile chronic arthritis were studied. Sixteen of these were preceded by an infection (chi 2 = 20.14, p less than 0.001), mostly of the upper respiratory tract. In the 10 cases seen during an infection causative agents were identified in 5 (herpes simplex, rhinovirus, and on 3 occasions streptococcus). The total number of infections was not increased when compared with infection rates predicted by several reported studies. In the absence of clinical infection, specific antibody titres to a panel of microbial antigens were similar to those of a control group but with a trend toward higher titres in patients with hypergammaglobulinaemia. Interferon (IFN) responses were not defective, though sequential in-vitro IFN production from peripheral blood mononuclear cells (PBM) fluctuated considerably in the same patients, occasionally being absent with no obvious clinical correlate. IFN-alpha was induced by stimulation with Newcastle disease virus (NDV), and the mean responses of the patients were significantly greater than those of controls. IFN-gamma production on phytohaemagglutinin (PHA) stimulation was similar in patients and control groups. IFN was not detected in any of the sera from patients or controls.